Explaining import variety and quality: The role of the income distribution - Yo Chul Choi; David Hummels; Chong Xiang (Luxembourg Income Study (LIS), 2010)
In this paper we examine whether a generalized version of Flam and Helpman's (1987) model of vertical differentiation can reconcile three facts. One, countries import only a subset of available varieties. Two, import prices vary across exporters within narrow product categories. Three, US growth in both import variety and import price dispersion has occurred at the same time that the US income distribution has significantly widened. The generalized model maps cross-country differences in income distributions to variation in import variety and price variation. The theoretical predictions are examined and confirmed using panel data on import variety and prices, and detailed income distribution data from the Luxemborg Income Survey (LIS). Country pairs whose income distributions are growing more similar over time have growing similarity in the distribution of their import prices, and in the number of common export sources from which they buy.
Keywords: 330; Importnachfrage; Güter; Preis; Produktqualität; Einkommensverteilung; Welt; Ökonometrisches Modell